Characterisation of Malaysian avocado pulp oil obtained through mechanical press extraction - Aisyah Amini Amin; Aemelda Nastiyana Anak Adin; Mohamad Norisham Mohamad Rosdi; Fan Hui Yin; Syariena Arshad; Bangun Prajanto Nusantoro; Helmi Wasoh; Mohd Nasir Mohd Desa; Yanty Noorzianna Abdul Manaf (e-VIBS, Faculty of Science and Natural Resources, 2024)
This study aimed to determine the characteristics of pulp oil from Malaysian avocado (Persea americana) using mechanical press extraction. The quality of extracted crude oil was assessed for basic physicochemical parameters, and triacylglycerol (TAG) and fatty acid compositions. The extracted oil was in a liquid form at room temperature (25 °C), with dark green in colour. The iodine and free fatty acid values of the oil were 79.48 g I2/100 g oil and 1.66%, respectively. The oil was found to contain POL (21.37%) as the predominant TAG, followed by POO (14.42%), PLL (12.383%), and PPO (9.764%). The oil had high amounts of total unsaturated fatty acids (68.09%), mainly contributed by oleic acid (34.53%), followed by palmitic (30.08%), linoleic (19.12%), and palmitoleic (11.06%) acids.